Training to Improve Clinical Specimen Collection and Antimicrobial Resistance (AMR) Diagnostics and Surveillance in Ethiopia. (October 2020) - Stevenson, Kurt; Balada-Llasat, Joan-Miquel; Kue, Jennifer; Bersani, Ashley; Yimer, Getnet; Wang, Shu-Hua; Gebreyes, Wondwossen; Alebachew, Gebrie; Dinku, Surafel Fentaw; Abubeker, Rajiha; Seyoum, Eyasu; Hazim, Carmen; et al.
Abstract : Background: Antimicrobial resistance (AMR) is an increasingly critical global public health challenge. An initial step in prevention is the understanding of resistance patterns with accurate surveillance. To improve accurate surveillance and good clinical care, we developed training materials to improve the appropriate collection of clinical culture samples in Ethiopia. Methods: Specimen-collection training materials were initially developed by a team of infectious diseases physicians, a clinical microbiologist, and a monitoring and evaluation specialist using a training of trainers (ToT) platform. Revisions after each training session were provided by Ethiopian attendees including the addition of regional and culturally relevant material. The training format involved didactic presentations, interactive practice sessions with participants providing feedback and training to each other and the entire group as well as assessments of all training activities. Results: Overall, 4 rounds of training were conducted from August 2017 to September 2019. The first 2 rounds of training were conducted by The Ohio State University (OSU) staff, and Ethiopian trainers conducted the last 2 rounds. Initial training was primarily in lecture format outlining use of microbiology laboratory findings in clinical practice and steps for collecting specimens correctly. Appropriate specimen collection was demonstrated and practiced. Essential feedback from this early audience provided input for the final development of the training manual and visual aids. The ToT for master trainers took place in July 2018 and was conducted by OSU staff. In sessions held in February and August 2019, these master trainers provided training to facility trainers, who provide training to personnel directly responsible for specimen collection. In total, 144 healthcare personnel (including physicians, nurses, and laboratory staff), from 12 representative Ethiopian public and academic hospitals participated in the trainings. Participants were satisfied with the quality of the training (typically ranked >4.5 of 5.0) and strongly agreed that the objectives were clearly defined and that the information was relevant to their work. Posttraining scores increased by 23%. Conclusions: Training materials for clinical specimen collection have been developed for use in low- and middle-resource settings and with initial pilot testing and adoption in Ethiopia. The trainings were well accepted, and Ethiopian personnel were able to successfully lead the trainings and improve their knowledge and skills regarding specimen collection. The materials are being finalized in an online format for easier open access dissemination. Further studies are planned to determine the effectiveness of the trainings in improving the quality of clinical specimen submissions to the microbiology laboratory. Funding: None Disclosures: None